RE: Mesocycle progression in hypertrophy: volume versus intensity - Minor, B.; Helms, E.; Schepis, J. (Strength and Conditioning Journal, 2020)
Letter to the Editor Original article: Israetel, M., Feather, J., Faleiro, T. V., & Juneau, C. E. (2020). Mesocycle progression in hypertrophy: Volume versus intensity. Strength & Conditioning Journal, 42(5), 2-6.